Modelling of Urban Stormwater Drain with Orifice Flow in Series using SWMM - Merry Shi Ting, Tang (N.A., 2025)
Stormwater infrastructure requires modification to solve the urban flooding problem due to increasing stormwater runoff rate and volume in the urban areas. This study investigated an urban drain (0.5 m W x 0.5 m D x 170 m L) divided into compartments with orifice flow restrictors to detain stormwater, subjecting the drain to three drain slopes of 0%, 0.2%, and 0.4%. The orifices had diameters ranging from 0.1 m to 0.5 m. A design rainfall of 5 minutes with a 10-year ARI intensity and three historical rainfalls were selected for stormwater flow analyses. Two rows of 12-unit terrace houses with 4,227 m² land area were selected as the study area. Three interventions were designed, namely: Drain with Single-Orifice (Scenario 1), Double-Orifice (Scenario 2), and Triple-Orifice (Scenario 3). The research utilized SWMM version 5.0 to effectively simulate the unique characteristics of the three interventions, creating sub-models that allowed for a detailed evaluation of the flow conditions in the study area and the impacts of different slopes, orifice sizes, numbers of orifice at varied locations. Overall, the 0.2% slope for design rainfall had the highest peak flow at the downstream end, while the 0% and 0.4% slopes peaked at the upstream end; for historical rainfall, the highest peak flow occurred at the downstream end for the 0% and 0.4% slopes, with the 0.4% slope also showing the highest peak flow upstream. However, the peak water level for the 0.1 m diameter result was the highest and decreased with increasing orifice diameter from 0.2 m to 0.5 m. The results indicated that Scenario 3, featuring diameters from 0.3 m to 0.5 m at a 0.2% slope, demonstrated the best performance with consistent reductions in peak flow and water level hydrographs, and no overflow was predicted for this scenario.